Visual Analytics Pola Kerja Praktik Mahasiswa Menggunakan Tableau (Studi Kasus: Politeknik Caltex Riau) - Ardiyanto Ardiyanto; Yuliska Yuliska (Jurnal Komputer Terapan, 2026)
The implementation of student internships is an important component of vocational education that bridges academic learning and industry needs. However, internship data are generally still presented in tabular form, making it difficult to comprehensively identify placement patterns, implementation trends, and industry characteristics. This study aims to apply a visual analytics approach to analyze trends and characteristics of student internship placements at Politeknik Caltex Riau. The data used consist of historical internship records over four academic semesters, including study programs, industry types, industry locations, internship durations, and industry partners. The research method includes data preprocessing, data transformation, and the development of an interactive visual dashboard using Tableau. The analysis results indicate fluctuating internship implementation trends across academic years, with student placements concentrated in specific industrial sectors and geographic regions. In addition, several industry partners were consistently identified as dominant internship providers. The findings demonstrate that the visual analytics approach can support more intuitive identification of internship placement patterns, improve program evaluation, and enhance data-driven decision-making in internship management.